The Influence of knowledge on decompression through diving behaviour of traditional diver at Barrang Lompo island - Ahdar, A.Rifkah Fauziah; Wahyu, Atjo; Mallongi, Anwar (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Background: Divers in coastal areas are not aware of the risks of diving encountered which can disrupt health and threaten the safety of their lives. Diving activities have a long-term effect on the physiology of the human body. The diseases associated with diving are Barotrauma and decompression. Barrang Lompo Island Health Center data in Makassar City shows that the prevalence of accidents for traditional divers in 2011-2017 in Makassar City is quite high, with paralysis of 85 people, dead as many as 70 people. Methods: The type of research used was observational using a cross sectional study design. The population used in this study were traditional divers in the population. The population was a traditional diver on the Barang Lompo island with 124 divers. 100 samples were selected using accidental sampling techniques. Data collection was carried out by officers in the field and using questionnaires, microtoise and weight scales. The level of knowledge and decompression was measured using a questionnaire, while IMT measurements used microtoise and weight scales. Results: groups that tend to experience severe decompression are divers with sufficient level of knowledge (45.8%) and having unsafe diving behaviour habits (45.%) there is an influence of knowledge on diving behaviour with p value 0.05, and diving behaviour towards decompression p value of 0.037 <0.05 , indirectly and found an indirect influence of knowledge on decompression through diving behaviour. Conclusion: there is a direct influence of knowledge on diving behaviour and the indirect influence of knowledge on decompression through diving behaviour.